Water conservation and the common pool problem: Can pricing address free-riding in residential hot water consumption? - Mikael Elinder; Xiao Hu; Che-yuan Liang (Research Institute of Industrial Economics (IFN), 2021)
Water is an increasingly scarce resource. It is often distributed such that consumers do not face any marginal cost of consumption, creating a common pool problem. For instance, tenants in multi-family buildings can often consume both hot and cold water at zero marginal cost. Using high-frequency data over many years, we analyze how the introduction of apartment-level metering and billing (IMB) affects hot water consumption. We find that introducing a marginal cost, reflecting the market price, decreases consumption drastically by 26%. Hence, price interventions can curb free-riding behavior and help the conservation of cheap but precious resources. Our results also show that heavy water users in the top consumption quartile account for 72% of the reduction. Moreover, cost-benefit calculations indicate that IMB for hot water is a cost-effective policy tool for reducing water and energy consumption.
Keywords: D12; Q21; Q25; Q28; 330; Residential water consumption; Water conservation; Common pool problem; Free-riding; Individual metering and billing